Superstrong solid base catalyst as well as preparation method and application thereof

By developing alkali metal modified mesoporous nano MgO as a super-strong solid alkali catalyst, the problems of catalyst toxicity and insufficient alkalinity in the existing carbon glycoside synthesis methods are solved, and efficient and green carbon glycoside synthesis is achieved, which is suitable for industrial applications.

CN119425657APending Publication Date: 2025-02-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310967614.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing carbon glycoside synthesis methods, the toxicity, corrosiveness and flammability of catalysts such as tetrahydropyrrole and triethylamine limit the application of this process, and the alkalinity of solid alkalinity such as magnesium oxide and calcium oxide is insufficient, resulting in reactions. Inefficient.

Method used

Developed a super-strong solid alkali catalyst, including mesoporous nano MgO and alkali metals supported on its surface (such as K, Na, Cs), prepared by urea-assisted precipitation and air calcination, for catalyzing β-carbon glycosidone ketones and Aldehyde condensation reaction of aldehyde compounds.

Benefits of technology

The catalyst has a super alkaline position, can efficiently catalyze the aldol condensation reaction, the product is easy to separate, the catalyst can be reused, the process is green and economical, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004377338240000011
    Figure BDA0004377338240000011
  • Figure BDA0004377338240000071
    Figure BDA0004377338240000071
  • Figure BDA0004377338240000072
    Figure BDA0004377338240000072
Patent Text Reader

Abstract

The invention discloses a superstrong solid base catalyst as well as a preparation method and application thereof. Mesoporous nano MgO is obtained through urea-assisted precipitation and air atmosphere calcination, then the freshly prepared mesoporous nano MgO is soaked in an alkali metal salt solution, and a series of superstrong solid base catalysts with different alkali metal loading capacities are obtained through calcination and activation. Beta-carbon glycoside ketone and an aldehyde compound raw material without alpha hydrogen are subjected to aldol condensation reaction under the promotion of the prepared superstrong solid base catalyst to obtain a carbon glycoside product with an alpha, beta-unsaturated carbonyl structure, the separation yield of the product is 90% or above, and the reaction performance is not obviously reduced after the catalyst is recycled for ten times. The method has the advantages that the method is simple in operation and low in cost, has super-strong alkaline sites, can efficiently catalyze the aldol condensation reaction of the beta-carbon glycoside ketone to obtain the target product carbon glycoside without the assistance of amine compounds to form enamine, and is simple in reaction system separation, reusable, green in process, simple to operate and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a super strong solid base catalyst and a preparation method and application thereof, belonging to the field of catalysis. Background Art

[0002] Sugars and their derived chemicals are widely available and renewable. As the cornerstone of synthetic modules, they can be used to obtain a series of bulk compound products through the conversion process. They have attracted extensive attention from researchers in recent years. Among them, glycosides are sugar-containing derivatives formed by the condensation of monosaccharide or oligosaccharide molecules with another non-sugar compound or functional group through glycosidic bonds. According to the different atoms in the glycosidic bond, they are divided into oxygen glycosides, nitrogen glycosides, glucosides and carbon glycosides. Carbon glycosides are a class of compounds in which the exocyclic atom connected to the anomeric carbon of the glycosidic bond is a carbon atom. Compared with oxygen glycoside compounds, the carbon-carbon bond in carbon glycosides replaces the carbon-oxygen bond of hemiacetal, thereby significantly improving the stability against acid hydrolysis and enzyme hydrolysis. At present, carbon glycoside derivatives have been reported to be used as synthetic anti-tumor drugs, antibiotics, antibacterial and anti-inflammatory agents, surfactants, and anti-aging active substances. Therefore, it is of great significance to explore the synthesis and utilization strategies of carbon glycosides in basic and applied research.

[0003] The Lubineau research group first reported the reaction process of D-glucose and acetylacetone condensing in sodium bicarbonate solution to obtain β-carbon glucosides (Chem. Commun., 2000, 2049-2050). The researchers of L'Oreál expanded the sugar substrates and used D-xylose, D-lactose, D-trehalose, D-arabinose and 3-deoxy-D-arabinose in addition to glucose. Under similar conditions, the corresponding β-D-carbon glucosides were obtained with excellent to moderate yields (WO2002051828; EP 1589010).

[0004] The process of synthesizing carbon glycosides from unprotected sugars is as follows:

[0005]

[0006] It can be seen from the process that β-carbon glucosides can further achieve carbon chain growth through aldol condensation reaction. Foley et al. used β-carbon glucosides as substrates, and under the catalysis of tetrahydropyrrole, carried out aldol condensation reaction with aldehydes of different carbon chain lengths to obtain different linear and cyclic carbon glycosides, among which the enamine intermediate formed by tetrahydropyrrole and glucosides is the key to the efficient progress of the process. However. The toxicity, corrosiveness and flammability of tetrahydropyrrole limit the application of this process. Wang et al. also achieved the above reaction process using L-proline and triethylamine as catalysts, but the high flammability, volatility, respiratory toxicity and mechanical shock explosion hazard of triethylamine also limit its application. Tamara et al. used L-proline and solid bases such as magnesium oxide and calcium oxide to catalyze the reaction of β-carbon glucosides with aromatic aldehydes of different structures, and successfully achieved the aldol condensation reaction catalyzed by enamine-solid base. However, when the amount of L-proline is small (0.15 molar equivalent), the reaction process takes 2 days to complete; when the amount of L-proline is increased to 1 equivalent, the reaction time can be shortened to 6.5h (ACS Sustainable Chem. Eng., 2018, 6, 7810-7817; ACS Sustainable Chem. Eng., 2018, 6, 11196-11199; US20210163384). Although the solid base can be recycled, it will consume a large amount of L-proline, resulting in certain bottlenecks in product separation, waste treatment and economic costs when the method is further scaled up. Through the analysis of the reaction process mechanism, since the alkalinity of solid bases such as magnesium oxide and calcium oxide cannot meet the requirements of the aldol condensation reaction of β-carbon glucoside ketone, amine substances must be added to react with the substrate to form an enamine structure in order to ensure the smooth progress of the reaction. Therefore, in order to develop a greener synthesis method for carbon glycosides without the assistance of amine compounds, it is necessary to design and synthesize super-strong solid base catalysts to directly catalyze the aldol condensation reaction between substrates. Summary of the invention

[0007] The present invention aims to provide a method for preparing a super-strong solid base catalyst, and to apply the method to catalyze the aldol condensation reaction to prepare carbon glycosides. The method has high yield, easy separation of products, simple catalyst synthesis steps and reusability, and the process is green, economical and suitable for industrial production.

[0008] According to one aspect of the present application, a super strong solid base catalyst is provided, wherein the super strong solid base catalyst comprises mesoporous nano-MgO and an alkali metal supported on the surface of the mesoporous nano-MgO;

[0009] The alkali metal is selected from at least one of K, Na, and Cs;

[0010] The pore size of the super strong solid base catalyst is 2 to 10 nm;

[0011] The particle size of the super strong solid base catalyst is 50 to 500 nm.

[0012] The alkali metal is present in the solid base catalyst in the form of alkali metal oxide or alkali metal cation;

[0013] In the super strong solid base catalyst, the content of the alkali metal is 0.5-5.0wt%.

[0014] According to another aspect of the present application, a method for preparing the above-mentioned super strong solid base catalyst is provided, comprising the following steps:

[0015] (1) mixing an aqueous solution containing a Mg precursor with an aqueous solution containing urea, reacting, drying I, and calcining I to obtain mesoporous nano-MgO;

[0016] (2) The mesoporous nano-MgO obtained in (1) is immersed in an aqueous solution containing an alkali metal precursor, dried II, and calcined II to obtain the super strong solid base catalyst.

[0017] The Mg precursor is selected from at least one of magnesium acetate, magnesium chloride, magnesium nitrate and magnesium oxalate;

[0018] In the aqueous solution containing the Mg precursor, the content of the Mg precursor is 0.1 to 1.0 mol / L;

[0019] In the aqueous solution containing urea, the content of urea is 0.1-2.0 mol / L;

[0020] The volume ratio of the aqueous solution containing the Mg precursor to the aqueous solution containing urea is 1:1 to 5 / 1;

[0021] The drying temperature is 50-110°C;

[0022] The temperature of the calcination I is 300-800°C;

[0023] The calcination time is 0.5 to 6 hours;

[0024] The atmosphere of the calcination I is an air atmosphere.

[0025] The alkali metal precursor is selected from at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, potassium bicarbonate, cesium hydroxide, cesium carbonate, and cesium bicarbonate;

[0026] In the aqueous solution containing the alkali metal precursor, the content of the alkali metal precursor is 0.01 to 0.2 mol / L;

[0027] The solid-to-liquid ratio of the mesoporous nano-MgO to the aqueous solution containing the alkali metal precursor is 1:1 to 1:10;

[0028] The temperature of calcining II is 300-800°C;

[0029] The calcination II takes 3 to 10 hours.

[0030] Specifically, for example:

[0031] Preparation of super strong solid base catalyst: Add 200mL of magnesium acetate solution (0.5mol / L) to a round bottom flask, heat to reflux, and pump 100mL of 1.0mol / L urea solution through a peristaltic pump while stirring. The pumping speed is set to 5mL / min. After the pumping is completed, continue to reflux and stir for 6.0h. After cooling to room temperature, the white precipitate was collected by centrifugation and dried at 110°C overnight. The obtained solid product was heated to 600°C at 2°C / min and calcined for 3h in an air atmosphere to obtain mesoporous nano-MgO, recorded as meso-nano-MgO; a series of alkali metal carbonate solutions (Na2CO3, K2CO3, Cs2CO3) of different concentrations were prepared, and 10mL of solutions of different concentrations were respectively measured and added with stirring while adding freshly prepared meso-nano-MgO (2.0g), stirred at room temperature overnight, filtered, and dried. The obtained solid product was heated to 600°C at 2°C / min and calcined for 5h in an air atmosphere to obtain super strong solid alkali Na / meso-nano-MgO, K / meso-nano-MgO, Cs / meso-nano-MgO, which were sealed and stored.

[0032] According to another aspect of the present application, there is provided a use of the super strong solid base catalyst according to claim 1, characterized in that:

[0033] Used to prepare carbon glycoside products with α, β-unsaturated carbonyl structure;

[0034] The process includes:

[0035] The raw materials of β-carbon glycoside ketone and aldehyde compound without α hydrogen are contacted with the super strong solid base catalyst in an alcohol solvent to carry out aldol condensation reaction to obtain carbon glycoside product with α, β-unsaturated carbonyl structure.

[0036] The β-carbon glycoside is selected from at least one of β-carbon xyloside, β-carbon glucosidase, β-carbon galactosidase, β-carbon mannoside, β-carbon rhamnoside, β-carbon arabinoside and β-carbon bioglycoside;

[0037] The aldehyde compound not containing alpha hydrogen is selected from at least one of benzaldehyde, p-tolualdehyde, p-hydroxybenzaldehyde, o-hydroxybenzaldehyde, p-methoxybenzaldehyde, o-methoxybenzaldehyde, o-chlorobenzaldehyde, p-aminobenzaldehyde, p-nitrobenzaldehyde, 4-carboxybenzaldehyde, vanillic aldehyde, veratraldehyde, cinnamaldehyde, protocatechuic aldehyde, 1-naphthaldehyde, 2-naphthaldehyde, furfural, 5-hydroxymethylfurfural, 2-pyridinecarboxaldehyde and 2-thiophenecarboxaldehyde;

[0038] The alcohol solvent is selected from at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol and tert-butanol.

[0039] The mass ratio of the β-carbon glycoside ketone to the alcohol solvent is 1 to 50:100;

[0040] Optionally, the mass ratio of the carbon glycoside to the alcohol solvent is 5 to 25:100;

[0041] The molar ratio of the β-carbon glycoside ketone to the aldehyde compound not containing α hydrogen is 1:10 to 10:1;

[0042] Optionally, the molar ratio of the β-carbon glycoside ketone to the aldehyde compound not containing α hydrogen is 1:5-1;

[0043] The mass ratio of the super strong solid base catalyst to the β-carbon glucoside ketone is 1 to 20:100;

[0044] Optionally, the mass ratio of the super strong solid base catalyst to the β-carbon glycoside ketone is 5 to 15:100.

[0045] The temperature of the aldol condensation reaction is 25 to 100° C.;

[0046] Optionally, the temperature of the aldol condensation reaction is 25-50°C.

[0047] The aldol condensation reaction time is 0.5 to 24 hours;

[0048] Optionally, the aldol condensation reaction time is 1 to 5 hours.

[0049] Specifically, for example:

[0050] The reaction raw materials of β-carbon glycoside ketone and aldehyde compound without α hydrogen in a molar ratio of 1 / 10 to 10 / 1, reaction solvent (the mass ratio of β-carbon glycoside ketone to solvent is 1 / 100 to 50 / 100), and prepared solid super base (the mass ratio of catalyst to β-carbon glycoside ketone is 1 / 100 to 20 / 100) are sequentially added into a reaction kettle, the reaction temperature is controlled to be 25 to 100° C., the reaction time is 0.5 to 24 hours, the reaction is cooled to room temperature after the reaction is finished, the catalyst is filtered to remove the catalyst, the solvent is removed by rotary evaporation, and the product is separated by column chromatography. By optimizing the process conditions, the conversion rate of β-carbon glycoside ketone can reach more than 99%, and the selectivity of the target product carbon glycoside can reach more than 98%.

[0051] Compared with the existing technical route, the method of the present invention has the following characteristics:

[0052] 1. Different from the liquid alkali, traditional alkaline earth metal oxides and amine compounds used in the past, the catalyst used in the present invention is alkali metal-modified mesoporous nano-MgO, which has super strong alkalinity and can efficiently catalyze the aldol condensation reaction. The reaction system is simple to separate and can be reused.

[0053] 2. In the method of the present invention, the catalyst preparation steps are controllable, the reaction conditions are mild and efficient, and the process is green and sustainable. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a transmission electron microscope photograph of the mesoporous nano-MgO in Example 1 of the present application, with a scale of 100 nm. DETAILED DESCRIPTION

[0055] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0056] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0057] Example 1 Preparation of Alkali Metal Modified Mesoporous Nano-MgO Super Solid Base Catalyst

[0058] Accurately weigh 21.5g of magnesium acetate tetrahydrate into a 1000mL three-necked round-bottom flask, add 200mL of deionized water and stir to dissolve to prepare a 0.5mol / L solution. Heat the oil bath to 110℃ and reflux, while stirring, pump 100mL of 1.0mol / L urea solution at a pumping rate of 5mL / min through a peristaltic pump. After the pumping is completed, continue to reflux and stir for 6.0h. After cooling to room temperature, collect the white precipitate by centrifugation, dry it at 110℃ overnight, and the solid product is heated to 600℃ at 2℃ / min, and calcined in an air atmosphere for 3h to obtain mesoporous nano-MgO, recorded as meso-nano-MgO; Figure 1This is a transmission electron microscope photograph of the mesoporous nano-MgO in Example 1 of the present application, with a scale of 100 nm.

[0059] The results of nitrogen physical adsorption characterization showed that the BET specific surface area of ​​the sample was 200 m 2 / g, BJH pore volume is 0.45cm 3 / g, the average pore size is 3.5nm, and transmission electron microscopy results show that the MgO particle size is 50nm.

[0060] A series of Na2CO3 solutions with different concentrations were prepared, and 10 mL of solution with different concentrations was respectively added with stirring to freshly prepared meso-nano-MgO (2.0 g). The mixture was stirred at room temperature overnight, filtered, and dried. The solid product was heated to 600°C at a rate of 2°C / min and calcined for 5 h in an air atmosphere to obtain a super strong solid base with a high sodium loading, which was recorded as 0.5wt% Na / meso-nano-MgO, 1.0wt% Na / meso-nano-MgO, 2.0wt% Na / meso-nano-MgO, 3.0wt% Na / meso-nano-MgO, 4.0wt% Na / meso-nano-MgO, and 5.0wt% Na / meso-nano-MgO, and sealed for use.

[0061] K / meso-nano-MgO and Cs / meso-nano-MgO with different loading amounts were prepared according to the above steps.

[0062] Example 2 Preparation of carbon glycoside by aldol condensation reaction of β-carbon glucosidone and furfural catalyzed by solid base

[0063] In this example, the effects of different solid base catalysts on the aldol condensation reaction between β-carbon glucosidone and furfural were studied. The product was separated and purified by silica gel column chromatography, and the product was qualitatively analyzed by nuclear magnetic resonance spectroscopy. The selectivity of the product was calculated according to the feed amount of β-carbon glucosidone, that is, the calculation formula of the reactant conversion rate and the product yield is as follows:

[0064]

[0065]

[0066] In a 15mL stainless steel reactor, β-glucosidone (0.44g, 2mmol), furfural (0.192g, 2mmol), 5mL anhydrous methanol and 0.04g solid base catalyst (the mass ratio of catalyst to β-glucosidone substrate is 10 / 100) were added in sequence, the reactor was sealed, nitrogen was replaced, magnetic stirring (500rpm), and the reaction was carried out at room temperature (25°C) for 12h. Stirring was stopped, the reactor was opened, the catalyst was filtered out, and the mixture was transferred to a pear-shaped bottle. The solvent was removed after rotary evaporation, and column chromatography was performed to separate the unreacted substrate and the generated product, and the NMR spectrum was qualitatively analyzed. The conversion rate and product yield were calculated according to the amount of reactants and products obtained by column chromatography, as shown in Table 1.

[0067] Table 1 Aldol condensation reaction between β-glucosidone and furfural catalyzed by different solid bases

[0068]

[0069]

[0070] Example 3 Aldol condensation reaction between β-glucosidone and furfural catalyzed by Cs / meso-nano-MgO with different Cs loadings

[0071] In this example, the effect of meso-nano-MgO modified with different Cs loadings on the aldol condensation reaction between β-glucosidone and furfural was studied. The method in Example 1 was used to perform qualitative and quantitative analysis of the reaction products.

[0072] In a 15mL stainless steel reactor, β-carboglucoside (0.44g, 2mmol), furfural (0.192g, 2mmol), 5mL anhydrous methanol and 0.04g of Cs / meso-nano-MgO with different Cs loadings (the mass ratio of catalyst to β-carboglucoside substrate is 10 / 100) were added in sequence, the reactor was sealed, nitrogen was replaced, magnetic stirring (500rpm), and the reaction was carried out at room temperature (25°C) for 12h. Stirring was stopped, the reactor was opened, the catalyst was filtered out, and the mixture was transferred to a pear-shaped bottle. The solvent was removed after rotary evaporation, and column chromatography was performed to separate the unreacted substrate and the generated product, and the NMR spectrum was qualitatively analyzed. The conversion rate and product yield were calculated based on the amount of reactants and products obtained by column chromatography, as shown in Table 2.

[0073] Table 2 Aldol condensation reaction between β-glucosidone and furfural catalyzed by Cs / meso-nano-MgO

[0074]

[0075] Example 4 Effect of reaction temperature on the aldol condensation reaction between β-glucosidone and furfural

[0076] In this example, the effect of reaction temperature on the aldol condensation reaction between β-glucosidone and furfural under the catalysis of 2.0wt% Cs / meso-nano-MgO was studied. The method in Example 1 was used to conduct qualitative and quantitative analysis of the reaction product.

[0077] In a 15mL stainless steel reactor, β-carbon glucosidone (0.44g, 2mmol), furfural (0.192g, 2mmol), 5mL anhydrous methanol and 0.04g of 2.0wt% Cs / meso-nano-MgO (the mass ratio of catalyst to β-carbon glucosidone substrate is 10 / 100) were added in sequence, the reactor was sealed, nitrogen was replaced, the oil bath was preheated to the specified temperature, and the reaction was carried out under magnetic stirring (500rpm) for 12h. Stirring was stopped, cooled to room temperature, the reactor was opened, the catalyst was filtered out, transferred to a pear-shaped bottle, the solvent was removed after rotary evaporation, column chromatography was performed to separate the unreacted substrate and the generated product, and the NMR spectrum was qualitatively analyzed. The conversion rate and product yield were calculated according to the amount of reactants and products obtained by column chromatography, as shown in Table 3.

[0078] Table 3 Effect of reaction temperature on the aldol condensation reaction between β-glucosidone and furfural

[0079]

[0080] Example 5 Effect of reaction time on the aldol condensation reaction between β-glucosidone and furfural

[0081] In this example, the effect of reaction time on the aldol condensation reaction between β-glucosidone and furfural under the catalysis of 2.0wt% Cs / meso-nano-MgO at a reaction temperature of 50°C was studied. The method in Example 1 was used to conduct qualitative and quantitative analysis of the reaction products.

[0082] In a 15mL stainless steel reactor, β-carbon glucosidone (0.44g, 2mmol), furfural (0.192g, 2mmol), 5mL anhydrous methanol and 0.04g of 2.0wt% Cs / meso-nano-MgO (the mass ratio of catalyst to β-carbon glucosidone substrate is 10 / 100) were added in sequence, the reactor was sealed, nitrogen was replaced, the oil bath was preheated to 50°C, and the reaction was carried out under magnetic stirring (500rpm) for a certain time. Stirring was stopped, cooled to room temperature, the reactor was opened, the catalyst was filtered out, transferred to a pear-shaped bottle, the solvent was removed after rotary evaporation, column chromatography was performed to separate the unreacted substrate and the generated product, and the NMR spectrum was qualitatively analyzed. The conversion rate and product yield were calculated according to the amount of reactants and products obtained by column chromatography, as shown in Table 4.

[0083] Table 4 Effect of reaction time on the aldol condensation reaction between β-glucosidone and furfural

[0084]

[0085] Example 6 Cyclic performance of Cs / meso-nano-MgO catalyst

[0086] In this example, the recycling performance of 2.0wt% Cs / meso-nano-MgO catalyst in the aldol condensation reaction between β-glucosidone and furfural was studied. The method in Example 1 was used to conduct qualitative and quantitative analysis of the reaction products.

[0087] In a 100mL stainless steel reactor, β-carbon glucosidone (1.10g, 5.0mmol), furfural (0.48g, 6.0mmol), 25mL anhydrous methanol and 0.11g of 2.0wt% Cs / meso-nano-MgO (the mass ratio of catalyst to β-carbon glucosidone substrate is 10 / 100) are added in sequence, the reactor is sealed, nitrogen is replaced, the oil bath is preheated to 50°C, and the reaction is carried out for a certain time under magnetic stirring (500rpm). Stop stirring, cool to room temperature, open the reactor, filter and remove the catalyst, transfer to a pear-shaped bottle, remove the solvent after rotary evaporation, perform column chromatography to separate the unreacted substrate and the generated product, perform nuclear magnetic resonance spectroscopy qualitative analysis, and calculate the conversion rate and product yield according to the amount of reactants and products obtained by column chromatography; the separated catalyst is washed three times with anhydrous methanol, vacuum dried overnight, calcined at 600°C for 5h in an air atmosphere, and the next batch of reactions is carried out. The recycling performance is shown in Table 5.

[0088] Table 5 Cyclic performance of Cs / meso-nano-MgO catalyst

[0089]

[0090]

[0091] Example 7 Aldol condensation reaction between different β-carbon glycosides and furfural

[0092] In this example, the aldol condensation reaction between different β-carbon glucosides and furfural was studied under the catalysis of 2.0 wt% Cs / meso-nano-MgO at a reaction temperature of 50° C. The method in Example 1 was used to perform qualitative and quantitative analysis of the reaction products.

[0093] In a 15mL stainless steel reactor, β-carboglycoside (2mmol), furfural (0.192g, 2mmol), 5mL anhydrous methanol and equivalent 2.0wt% Cs / meso-nano-MgO (the mass ratio of catalyst to β-carboglycoside substrate is 10 / 100) were added in sequence, the reactor was sealed, nitrogen was replaced, the oil bath was preheated to 50°C, and the reaction was carried out under magnetic stirring (500rpm) for 5h. Stirring was stopped, cooled to room temperature, the reactor was opened, the catalyst was filtered out, transferred to a pear-shaped bottle, the solvent was removed after rotary evaporation, column chromatography was performed to separate the unreacted substrate and the generated product, and the NMR spectrum was qualitatively analyzed. The conversion rate and product yield were calculated according to the amount of reactants and products obtained by column chromatography, as shown in Table 6.

[0094] Table 6 Aldol condensation reaction between different β-carbon glycosides and furfural

[0095]

[0096]

[0097] Example 8 Aldol condensation reaction between β-carbon glucosidone and a series of aldehyde compounds not containing α hydrogen

[0098] In this example, the aldol condensation reaction between β-carbon glucosidone and a series of aldehyde compounds without α hydrogen was studied under the catalysis of 2.0wt% Cs / meso-nano-MgO at a reaction temperature of 50° C. The qualitative and quantitative analysis of the reaction products was carried out using the method in Example 1.

[0099] In a 15mL stainless steel reactor, β-carbon glucosidone (0.44g, 2mmol), aldehyde compounds without α hydrogen (2mmol), 5mL anhydrous methanol and 0.40g of 2.0wt% Cs / meso-nano-MgO (the mass ratio of catalyst to β-carbon glucosidone substrate is 10 / 100) were added in sequence, the reactor was sealed, nitrogen was replaced, the oil bath was preheated to 50°C, and the reaction was carried out under magnetic stirring (500rpm) for 5h. Stirring was stopped, cooled to room temperature, the reactor was opened, the catalyst was filtered out, transferred to a pear-shaped bottle, the solvent was removed after rotary evaporation, column chromatography was performed to separate the unreacted substrate and the generated product, and the NMR spectrum was qualitatively analyzed. The conversion rate and product yield were calculated according to the amount of reactants and products obtained by column chromatography, as shown in Table 7.

[0100] Table 7 Aldol condensation reaction between β-carbon glycosides and a series of aldehyde compounds without α hydrogen

[0101]

[0102]

[0103] In summary, the present invention provides a method for preparing carbon glycosides by catalyzing aldol condensation reaction with super-strong solid base. The specific process includes obtaining mesoporous nano-MgO by urea-assisted precipitation and air atmosphere calcination, then impregnating the freshly prepared mesoporous nano-MgO with an alkali metal salt solution, calcining and activating to obtain a series of super-strong solid base catalysts with different alkali metal loadings; the raw materials of β-carbon glycoside ketone and aldehyde compounds without α hydrogen are subjected to aldol condensation reaction under the promotion of the super-strong solid base catalyst prepared above to obtain carbon glycoside products with α, β-unsaturated carbonyl structure, and the product separation yield is above 90%, and the catalyst is recycled ten times without obvious decrease in reaction performance. The alkali metal-modified mesoporous nano-MgO used in the present invention has super-strong alkaline sites, can efficiently catalyze the aldol condensation reaction to obtain the target product carbon glycoside, the reaction system is simple to separate and can be reused, the process is green, the cost is low, and it has industrial prospects.

[0104] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A super strong solid base catalyst, characterized in that: The super strong solid base catalyst comprises mesoporous nano-MgO and an alkali metal loaded on the surface of the mesoporous nano-MgO; The alkali metal is selected from at least one of K, Na, and Cs; The pore size of the super strong solid base catalyst is 2 to 10 nm; The particle size of the super strong solid base catalyst is 50 to 500 nm.

2. A super strong solid base catalyst according to claim 1, characterized in that: The alkali metal is present in the solid base catalyst in the form of an alkali metal oxide or an alkali metal cation; In the super strong solid base catalyst, the content of the alkali metal is 0.5-5.0wt%.

3. A method for preparing the super strong solid base catalyst according to any one of claims 1 or 2, characterized in that: The following steps are involved: (1) mixing an aqueous solution containing a Mg precursor with an aqueous solution containing urea, reacting, drying I, and calcining I to obtain mesoporous nano-MgO; (2) The mesoporous nano-MgO obtained in (1) is immersed in an aqueous solution containing an alkali metal precursor, dried II, and calcined II to obtain the super strong solid base catalyst.

4. The preparation method according to claim 3, characterized in that: The Mg precursor is selected from at least one of magnesium acetate, magnesium chloride, magnesium nitrate and magnesium oxalate; In the aqueous solution containing the Mg precursor, the content of the Mg precursor is 0.1 to 1.0 mol / L; In the aqueous solution containing urea, the content of urea is 0.1-2.0 mol / L; The volume ratio of the aqueous solution containing the Mg precursor to the aqueous solution containing urea is 1:1 to 5:1; The drying temperature is 50-110°C; The calcination temperature is 300-600°C; The calcination time is 0.5 to 6 hours; The atmosphere of the calcination I is an air atmosphere.

5. The preparation method according to claim 3, characterized in that: The alkali metal precursor is selected from at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide, potassium carbonate, potassium bicarbonate, cesium hydroxide, cesium carbonate, and cesium bicarbonate; In the aqueous solution containing the alkali metal precursor, the content of the alkali metal precursor is 0.01 to 0.2 mol / L; The solid-to-liquid ratio of the mesoporous nano-MgO to the aqueous solution containing the alkali metal precursor is 1:1 to 1:10; The temperature of calcining II is 300-800°C; The calcination II takes 3 to 10 hours.

6. An application of the super strong solid base catalyst according to claim 1, characterized in that: Used to prepare carbon glycoside products with α, β-unsaturated carbonyl structure; The process includes: The raw materials of β-carbon glycoside ketone and aldehyde compound without α hydrogen are contacted with the super strong solid base catalyst in an alcohol solvent to carry out aldol condensation reaction to obtain carbon glycoside product with α, β-unsaturated carbonyl structure.

7. The use according to claim 6, characterized in that: The β-carbon glycoside is selected from at least one of β-carbon xyloside, β-carbon glucosidase, β-carbon galactosidase, β-carbon mannoside, β-carbon rhamnoside, β-carbon arabinoside and β-carbon bioglycoside; The aldehyde compound not containing alpha hydrogen is selected from at least one of benzaldehyde, p-tolualdehyde, p-hydroxybenzaldehyde, o-hydroxybenzaldehyde, p-methoxybenzaldehyde, o-methoxybenzaldehyde, o-chlorobenzaldehyde, p-aminobenzaldehyde, p-nitrobenzaldehyde, 4-carboxybenzaldehyde, vanillic aldehyde, veratraldehyde, cinnamaldehyde, protocatechuic aldehyde, 1-naphthaldehyde, 2-naphthaldehyde, furfural, 5-hydroxymethylfurfural, 2-pyridinecarboxaldehyde and 2-thiophenecarboxaldehyde; The alcohol solvent is selected from at least one of methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol and tert-butanol.

8. The use according to claim 6, characterized in that: The mass ratio of the β-carbon glycoside ketone to the alcohol solvent is 1 to 50:100; Preferably, the mass ratio of the carbon glycoside to the alcohol solvent is 5 to 25:100; The molar ratio of the β-carbon glycoside ketone to the aldehyde compound not containing α hydrogen is 1:10 to 10:1; Preferably, the molar ratio of the β-carbon glycoside ketone to the aldehyde compound not containing α hydrogen is 1:5-1; The mass ratio of the super strong solid base catalyst to the β-carbon glucoside ketone is 1 to 20:100; Preferably, the mass ratio of the super strong solid base catalyst to the β-carbon glycoside ketone is 5 to 15:

100.

9. The use according to claim 6, characterized in that: The temperature of the aldol condensation reaction is 25 to 100° C.; Preferably, the temperature of the aldol condensation reaction is 25-50°C.

10. The use according to claim 6, characterized in that: The aldol condensation reaction time is 0.5 to 24 hours; Preferably, the aldol condensation reaction time is 1 to 5 hours.

Citation Information

Patent Citations

  • New C-Glycoside derivatives and uses thereof

    EP1589010A1

  • Compositions and Methods for Reducing Enones to Saturated Alcohols

    US20210163384A1

  • Novel c-glycoside derivatives and use thereof

    WO2002051828A2